Characterization of MCF-12A cell phenotype, response to estrogens, and growth in 3D. - Sweeney, Michael F.; Sonnenschein, Carlos.; Soto, Ana M. (2018)
Background: Three-dimensional cultures of mammary epithelial cells allow for biologically-relevant studies of the development of the mammary gland in rodents and humans under normal and pathological conditions, like carcinogenesis. Under these conditions, mammotropic hormones play significant roles in tissue morphogenesis. Therefore, a system that recreates the normal, hormonally responsive epithelium would be a valuable tool to study the normal state and its transition to carcinogenesis. MCF-12A cells have been claimed to be non-tumorigenic mammary epithelial cells with reported sensitivity to estrogens. In this study, we aimed at characterizing MCF-12A cells for use in a hormone-responsive 3D culture system to determine their usefulness as a tool to identify normal and abnormal microenvironmental cues.; Keywords: Estrogen response, 3D culture, Tissue morphogenesis.; Springer Open.